Wpływ zmian gospodarczych na działalność banków spółdzielczych na Śląsku Opolskim - Bryniarska, Teresa Izabela (Wydział Prawa i Administracji UAM, 1997)
The article undertakes trial of answering a question: How to define identification and quantification of influence of economy changes on cooperative banks activity in Opole Silesia at the time of transformation from real socialism to free market economy. To response this question simultaneously the following thesis have been verified: 1) Money market of cooperative banks is involved in segmentation, being divided into unstable credit action, market with stable credit action, and market with limited credit action. 2) Formation of money market of cooperetive banks has been effected by functional community factors. 3) Cooperative banks serve a local society. The article notices useful for professionals methods of econometric and describing statistics, serving to examine the money market of cooperative banks.
Identification and quantification of influence of economic changes on co-operative banks activity in Opole-Silesia